COMPETITIVE ABILITY OF INVASIVE WEED SPECIES AND THEIR INFLUENCE ON PHYTOCENOSE BIODIVERSITY - Shuvar, I.; Korpita, H.; Dudar, I.; Lipińska, H. (Bulletin of Lviv National Environmental University. Series Agronomy, 2022)
The global threat from the spread of invasive plant species leads to an imbalance of plant living conditions in the agrocenosis and depletion / destruction of biodiversity. Ukrainian scientists are conducting a research on the impact of alien species of flora in the context of environmental threats to phytoinvasions. Invasive plants are especially dangerous both for the integrity of natural ecosystems and for various areas of economic activity. Invasive plant species cause significant damage to agriculture, forestry and water management, nature reserve areas. Less common invasive plant species create one of the biggest environmental problems in the world. This is a scientifically proven fact, which is legally reflected both in international conventions and in the legislation of individual countries. The foundation of an ecosystem is made by its flora. Therefore, invasive plant species are a blow to its foundation. If climatic conditions are suitable for invasive plants, they have a huge competitive advantage over native species, as they have no or limited natural enemies/consumers and diseases in the local ecosystem that could deter their spread. Therefore, they simply squeeze out local species from the territories, dooming them to extinction. The extinction of native plant species leads to extinction of native species of animals, fungi and many microorganisms that have built ties with the aboriginal flora for thousands or millions of years. They are directly dependent on it and are organically interconnected. That is why the invasion of an alien species does not increase the number and activity of local biodiversity, but, on the contrary, leads to the death of a significant number of species of flora and fauna dominated by only one or more species of invasive plants. In Ukraine, the impact of non-native plants on the environment is growing every year. In terms of Adventist flora, Ukraine ranks first among other flora in the world. The spontaneous fraction of adventive flora of Ukraine has 830 species of vascular plants (including 18 % – archeophytes and 82 % – kenophytes), which is about 14 % of the total flora of the country, which has more than 6,000 species of vascular plants (including all aboriginal and adventitious species), as well as the main cultivated and wild plants.